Discovery of the Once-Weekly Glucagon-Like Peptide‑1 (GLP-1) Analogue Semaglutide - Lau, Jesper; Bloch, Paw; Schäffer, Lauge; Pettersson, Ingrid; Spetzler, Jane; Kofoed, Jacob; Madsen, Kjeld; Knudsen, Lotte Bjerre; McGuire, James; Steensgaard, Dorte Bjerre; Strauss, Holger Martin; Gram, Dorte X; et al. (Journal of medicinal chemistry, 2015)
Liraglutide is an acylated glucagon-like peptide-1 (GLP-1) analogue that binds to serum albumin in vivo and is approved for once-daily treatment of diabetes as well as obesity. The aim of the present studies was to design a once weekly GLP-1 analogue by increasing albumin affinity and secure full stability against metabolic degradation. The fatty acid moiety and the linking chemistry to GLP-1 were the key features to secure high albumin affinity and GLP-1 receptor (GLP-1R) potency and in obtaining a prolonged exposure and action of the GLP-1 analogue. Semaglutide was selected as the optimal once weekly candidate. Semaglutide has two amino acid substitutions compared to human GLP-1 (Aib8, Arg34) and is derivatized at lysine 26. The GLP-1R affinity of semaglutide (0.38 ± 0.06 nM) was three-fold decreased compared to liraglutide, whereas the albumin affinity was increased. The plasma half-life was 46.1 h in mini-pigs following i.v. administration, and semaglutide has an MRT of 63.6 h after s.c. dosing to mini-pigs. Semaglutide is currently in phase 3 clinical testing.